Dengue Serotype Cross-Reactive, Anti-E Protein Antibodies Confound Specific Immune Memory for 1 Year after Infection - Toh, Ying Xiu; Gan, Victor; Balakrishnan, Thavamalar; Zuest, Roland; Poidinger, Michael; Wilson, Solomonraj; Appanna, Ramapraba; Thein, Tun Linn; Ong, Adrian Kheng-Yeow; Ng, Lee Ching; Leo, Yee Sin; Fink, Katja (Frontiers in Immunology, 2014)
Dengue virus has four serotypes and is endemic globally in tropical countries. Neither a specific treatment nor an approved vaccine is available, and correlates of protection are not established. The standard neutralization assay cannot differentiate between serotype-specific and serotype cross-reactive antibodies in patients early after infection, leading to an overestimation of the long-term serotype-specific protection of an antibody response. It is known that the cross-reactive response in patients is temporary but few studies have assessed kinetics and potential changes in serum antibody specificity over time. To better define the specificity of polyclonal antibodies during disease and after recovery, longitudinal samples from patients with primary or secondary DENV-2 infection were collected over a period of one year. We found that serotype cross-reactive antibodies peaked three weeks after infection and subsided within one year. Since secondary patients rapidly produced antibodies specific for the virus envelope (E) protein, an E-specific ELISA was superior compared to a virus particle-specific ELISA to identify patients with secondary infections. Dengue infection triggered a massive activation and mobilization of both naïve and memory B cells possibly from lymphoid organs into the blood, providing an explanation for the surge of circulating plasmablasts and the increase in cross-reactive E protein-specific antibodies.